Comparison between Self-retaining retractor and conventional retractor in condylar fracture fixation (Cuestiones de Fisioterapia, 2025)
Aim: This study aims to compare the operative time efficiency between self-retaining retractors andconventional (Langenbeck) retractors during mandibular condyle fixation via the retromandibularapproach. Methodology: A total of 60 patients were divided into two groups: the study group (selfretaining retractor, n = 30) and the control group (Langenbeck retractor, n = 30). The primary outcomemeasured was total operative time. Secondary parameters included the number of assistants required,surgical field exposure, and visibility